Lesbian potentiality and feminist media in the 1970s - Samer, Rox (Duke University Press, 2022)
In Lesbian Potentiality and Feminist Media in the 1970s, Rox Samer explores how 1970s feminists took up the figure of the lesbian in broad attempts to reimagine gender and sexuality. Samer turns to feminist film, video, and science fiction literature, offering a historiographical concept called “lesbian potentiality”—a way of thinking beyond what the lesbian was, in favor of how the lesbian signified what could have come to be. Samer shows how the labor of feminist media workers and fans put lesbian potentiality into movement. They see lesbian potentiality in feminist prison documentaries that theorize the prison industrial complex’s racialized and gendered violence and give image to Black feminist love politics and freedom dreaming. Lesbian potentiality also circulates through the alternative spaces created by feminist science fiction and fantasy fanzines like The Witch and the Chameleon and Janus. It was here that author James Tiptree, Jr./Alice B. Sheldon felt free to do gender differently and inspired many others to do so in turn. Throughout, Samer embraces the perpetual reimagination of “lesbian” and the lesbian’s former futures for the sake of continued, radical world-building.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; cinéma; communication; discipline; histoire et politique; lesbianisme; personnes lesbiennes; périodes historiques; ressource en ligne; thématiques; études littéraires

Enjeux culturels et sociaux de la circulation de la chanson J’attendrai dans les années 1940 - Beaudet, Simon-Pierre; Savoie, Chantal (Mens. Revue d'histoire intellectuelle et culturelle, 2013)
Cette analyse aborde le cas singulier de la circulation de la chanson J’attendrai dans la culture des années 1940, dont l’analyse des variantes permet de cerner les rapports mouvants d’une chanson aux genres chansonniers et musicaux, aux goûts et aux pratiques du public, ainsi qu’à leur ancrage au sein des champs culturels nationaux. Elle permet même, parfois, de sonder les modalités de l’évolution des modèles des rapports sociaux entre les sexes présents dans différentes versions. Ce sont ainsi autant les enjeux artistiques, culturels, sociaux et intimes à l’oeuvre qui guident notre analyse de ce cas de transfert culturel, que le repérage de vecteurs permettant de formuler une équation de la circulation culturelle des chansons à succès.
https://www.researchgate.net/publication/281628540_Les_temps_sociaux
Keywords: 1900-1999; 1930-1939; 1940-1949; 1990-1999; amérique du nord; amériques; approches et analyses; arts; canada; chanson; culture populaire; discipline; histoire et politique; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; études littéraires

Radclyffe Hall: A life in the writing - Dellamora, Richard (University of Pennsylvania Press, 2011)
The Well of Loneliness is probably the most famous lesbian novel ever written, and certainly the most widely read. It contains no explicit sex scenes, yet in 1928, the year in which the novel was published, it was deemed obscene in a British court of law for its defense of sexual inversion and was forbidden for sale or import into England. Its author, Radclyffe Hall, was already well-known as a writer and West End celebrity, but the fame and notoriety of that one book has all but eclipsed a literary output of some half-dozen other novels and several volumes of poetry. In Radclyffe Hall: A Life in the Writing Richard Dellamora offers the first full look at the entire range of Hall's published and unpublished works of fiction, poetry, and autobiography and reads through them to demonstrate how she continually played with the details of her own life to help fashion her own identity as well as to bring into existence a public lesbian culture. Along the way, Dellamora revises many of the truisms about Hall that had their origins in the memoirs of her long-term partner, Una Troubridge, and that have found an afterlife in the writings of Hall's biographers. In detailing Hall's explorations of the self, Dellamora is the first seriously to consider their contexts in Freudian psychoanalysis as understood in England in the 1920s. As important, he uncovers Hall's involvement with other modes of speculative psychology, including Spiritualism, Theosophy, and an eclectic brand of Christian and Buddhist mysticism. Dellamora's Hall is a woman of complex accommodations, able to reconcile her marriage to Troubridge with her passionate affairs with other women, and her experimental approach to gender and sexuality with her conservative politics and Catholicism. She is, above all, a thinker continually inventive about the connections between selfhood and desire, a figure who has much to contribute to our own efforts to understand transgendered and transsexual existence today.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; discipline; europe; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; royaume-uni; régions géographiques; thématiques; études littéraires

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

A critique of postcolonial reason: Toward a history of the vanishing present - Spivak, Gayatri Chakravorty (Harvard University Press., 1999)
Are the “culture wars” over? When did they begin? What is their relationship to gender struggle and the dynamics of class? In her first full treatment of postcolonial studies, a field that she helped define, Gayatri Chakravorty Spivak, one of the world’s foremost literary theorists, poses these questions from within the postcolonial enclave. “We cannot merely continue to act out the part of Caliban,” Spivak writes; and her book is an attempt to understand and describe a more responsible role for the postcolonial critic. A Critique of Postcolonial Reason tracks the figure of the “native informant” through various cultural practices—philosophy, history, literature—to suggest that it emerges as the metropolitan hybrid. The book addresses feminists, philosophers, critics, and interventionist intellectuals, as they unite and divide. It ranges from Kant’s analytic of the sublime to child labor in Bangladesh. Throughout, the notion of a Third World interloper as the pure victim of a colonialist oppressor emerges as sharply suspect: the mud we sling at certain seemingly overbearing ancestors such as Marx and Kant may be the very ground we stand on. A major critical work, Spivak’s book redefines and repositions the postcolonial critic, leading her through transnational cultural studies into considerations of globality.
Keywords: 1900-1999; 1980-1989; arts; cours; discipline; fem1000; histoire; histoire et politique; international; premier cycle; périodes historiques; sciences humaines; sofia; thématiques; théories féministes; études culturelles; études littéraires; études postcoloniales

The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics–such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha–in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

In other worlds essays in cultural politics - Spivak, Gayatri Chakravorty (Routledge, 1988)
Dans cet ouvrage classique, Gayatri Chakravorty Spivak, l'une des théoriciennes de la culture les plus importantes et les plus influentes travaillant aujourd'hui, analyse la relation entre la langue, les femmes et la culture dans des contextes occidentaux et non occidentaux. Développant une intégration originale de puissantes méthodologies contemporaines - déconstruction, marxisme et féminisme - Spivak tourne ce nouveau modèle sur les grands débats de l'étude de la littérature et de la culture, assurant ainsi que In Other Worlds est devenu un outil précieux pour étudier notre propre monde et celui des autres cultures.
Keywords: 1900-1999; 1980-1989; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; histoire et politique; international; lit3220; premier cycle; périodes historiques; thématiques; théories féministes; théories littéraires; études littéraires; études postcoloniales

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
http://catalogue.bnf.fr/ark:/12148/cb349656237
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

La Québécoite: roman - Robin, Régine (Québec-Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Section: 200 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Sanaaq: roman - Nappaaluk, Mitiarjuk (Stanké, 1969)
« Sanaaq est le nom de l'héroine, dont on suit, tout au long du récit, les heurs et malheurs, avant et après l'arrivée des premiers Blancs en pays inuit. À l'image de Mitiarjuk, c'est une femme forte et équilibrée, sensible et déterminée, qui nous fait découvrir de l'intérieur, comme aucun Occidental, fût-il anthropologue, n'a encore pu le faire, la vie et la psychologie des Inuits confrontés à une nature extrême, à la nécessité du partage et à l'envahissement de leur territoire par les Blancs et leur civilisation. » – Résumé de Publications Nunavik.
Section: 303 p. ; 21 cm.
Keywords: 1900-1999; 1930-1939; 1940-1949; amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; littérature; littérature inuit; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; thématiques; études littéraires

Le torrent - Hébert, Anne (Beauchemin, 1950)
Un enfant prisonnier de sa mère, au cœur d’un domaine bruissant d’eaux sauvages (Le torrent) ; un instant de tendresse dérisoire, qui change à jamais la vie sage d’une ouvrière-tricoteuse (La robe corail) ; l’exode vécu comme une fête par une petite serveuse, enfin libre au milieu des dangers (Le printemps de Catherine) ; la visite quotidienne d’un homme frustré à sa sœur, qu’il espère chaque jour trouver morte (La maison de l’esplanade)... Si divers que soient les paysages, les milieux, les situations, ces nouvelles d’Anne Hébert sont toutes tendues par une même force : celle de la passion (amour ou haine) qui saisit l’être dans les premiers temps de son existence, qui ne pourra être "dite" parce que la famille, la société ou la solitude refusent cette parole, et qui ne se délivrera d’elle-même que dans la mort — meurtre ou suicide. On retrouvera, à la mesure de ces thèmes, les qualités que "Les chambres de bois" et les "Poèmes" avaient révélées : sens concret de l’instant, vigueur et brièveté de l’écriture, saveur terrienne des images et des mots.
Section: 171 pages
Keywords: 1900-1999; 1990-1999; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; littérature; maternité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études littéraires